PENGARUH BUDAYA PEMBATALAN TERHADAP CITRA AKUN @LAMBE TURAH DI KALANGAN PENGGUNA SOSIAL MEDIA DI INSTAGRAM - Ramadhan, Alfat Fadhil; ', Yasir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Cancel culture refers to participatory social activism that has become more common since the advent of social media. Cancel culture reflects how public opinion can have a big impact on a career as a public figure. Social media, especially Instagram, can create an environment where public figures are constantly monitored or become the center of attention and assessed by their followers. The aim of this research is to determine the influence of cancellation culture on the image of the @Lambe Turah account among social media users on Instagram. This research was conducted on Instagram social media followers of the @Lambe Turah account. This research uses a quantitative type of research. This is done because the type of data is quantitative. This research method uses quantitative methods because the data is ratio data and is the focus The purpose of this research is to determine the magnitude of the influence between the variables studied.This research was carried out using a survey method using a questionnaire and the analysis technique used was simple regression to examine the influence of cancellation culture on the image of the @Lambe Turah account among social media users on Instagram. The results of this research show that cancel culture has an influence on the image of the @Lambe Turah account. This is reinforced by the value of R2 = 60.6, which means that the contribution of cancel culture has a strong influence on the image of the @Lambe Turah account on Instagram social media. The user of the @Lambe Turah account also carries out grieving where social media users express disappointment with an action taken by someone and then post it on their social media account. This is often done by the @Lambe Turah account against public figures who do something unusual.